1992
DOI: 10.1093/cvr/26.5.487
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic effects of preconditioning in anaesthetised dogs and rats

Abstract: Short preconditioning periods of myocardial ischaemia protect the myocardium against the arrhythmogenic effects of a more prolonged occlusion. The optimum time for this preconditioning occlusion in rats is 3 min and protection is still apparent 30 min later. In dogs, the protective effect is especially clear with two short (5 min) coronary artery occlusions. The protection in this species lasts for less than 1 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
179
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(197 citation statements)
references
References 0 publications
14
179
0
4
Order By: Relevance
“…This protection against arrhythmias was similar to that we have obtained previously in the same model with ischaemic preconditioning (Végh et al, 1992a), and with the administration of NO donors (Gyorgy et al, 2000;Gonczi et al, 2009;Kiss et al, 2010). Furthermore, the present study confirmed the role of eNOS activation in the antiarrhythmic effect of simvastatin, since both the phosphorylation of eNOS (determined by Western blot) and Fluorescence intensity (arbitrary units) Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This protection against arrhythmias was similar to that we have obtained previously in the same model with ischaemic preconditioning (Végh et al, 1992a), and with the administration of NO donors (Gyorgy et al, 2000;Gonczi et al, 2009;Kiss et al, 2010). Furthermore, the present study confirmed the role of eNOS activation in the antiarrhythmic effect of simvastatin, since both the phosphorylation of eNOS (determined by Western blot) and Fluorescence intensity (arbitrary units) Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Under light anaesthesia (30 mg/kg intravenous sodium pentobarbitone, Sigma, St. Louis, MO, USA) the right femoral artery was prepared and catheterized, through which the dogs were further anaesthetized with a mixture of chloralose and urethane (60 and 200 mg/kg, respectively; Sigma, St. Louis, MO, USA) to maintain anaesthesia. The animals were then intubated and ventilated with room air using a Harvard respirator (Harvard Apparatus, Natick, MA, USA) at a rate and volume sufficient to maintain arterial blood gases and pH within physiological limits (Végh et al, 1992a). Body temperature was measured from the mid-oesophagus and maintained by a heating pad at 37 70.5 1C.…”
Section: Animals and Surgical Preparationmentioning
confidence: 99%
See 3 more Smart Citations